1997
DOI: 10.1016/s0014-5793(96)01410-x
|View full text |Cite
|
Sign up to set email alerts
|

Purification of ADAM 10 from bovine spleen as a TNFα convertase

Abstract: We have purified a protease with characteristics of TNFa convertase from bovine spleen membranes. Peptide sequencing of the purified protein identified it as ADAM 10 (Genbank accession no. Z21961). This metalloprotease cleaves a recombinant proTNFa substrate to mature TNFa, and can cleave a synthetic peptide substrate to yield the mature TNFa amino terminus in vitro. The enzyme is sensitive to a hydroxamate inhibitor of MMPs, but insensitive to phosphoramidon. In addition, cloned ADAM 10 mediates proTNFa proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
77
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 13 publications
4
77
0
Order By: Relevance
“…Certain released molecules can be cleaved by more than one enzyme, and some enzymes can cleave more than one substrate. For example, TNF-␣ cleavage can also be mediated by ADAM10 (23), and ␣-secretase activity for ␤-amyloid precursor protein has been attributed to TACE/ADAM17 (24) and ADAM9 (25). It is not known how the protease(s) select their substrate, because consensus cleavage sites have not been identified.…”
mentioning
confidence: 99%
“…Certain released molecules can be cleaved by more than one enzyme, and some enzymes can cleave more than one substrate. For example, TNF-␣ cleavage can also be mediated by ADAM10 (23), and ␣-secretase activity for ␤-amyloid precursor protein has been attributed to TACE/ADAM17 (24) and ADAM9 (25). It is not known how the protease(s) select their substrate, because consensus cleavage sites have not been identified.…”
mentioning
confidence: 99%
“…Moreover, expression of a mutant form of TACE in normal cells was shown to inhibit endogenous TACE function, indicating that the reduced TNF release in mutant T cells was due to a dominant negative effect of mutant TACE rather than the absence of other TACE-like enzymes (Solomon et al, 1999). Recent reports also implicated another ADAM family proteinase ADAM 10 as a TNF convertase (Lunn et al, 1997;Rosendahl et al, 1997). These results suggest that alternative pathways for the release of membranebound pro-TNF exist in certain types of cells.…”
Section: Introductionmentioning
confidence: 68%
“…[34][35][36] Although no direct comparison between the two markers has been performed, data from the literature indicate that CD69 could be far less specific than TNFa, because a significant proportion of CD69 þ cells do not produce cytokines. 37 Although TNFa secretion pathways have been reported that are independent of TACE, 38 most TNFa molecules are produced as cytoplasmic membrane proteins that are rapidly cleaved into a soluble form by TACE. [39][40][41] The use of specific TACE inhibitors has been associated with progressive accumulation of TNFa on the surface of the cytoplasmic membrane of TNFa producing cells, allowing for their specific and unequivocal identification.…”
Section: Discussionmentioning
confidence: 99%